(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background and aims: Chronic Kidney Disease (CKD) And Hypertension(HTN) Are Associated With Each Other Invariably And Each Can Cause Or Aggravate The Other.Hypertension Is A Strong Independent Risk Factor For ESRD And Contributes To The Disease Itself, Or Most Commonly, To Its Progression.24 Hour Ambulatory Blood Pressure Monitoring (ABPM) Is Superior To Clinic BP Monitoring In Predicting The Risk In Hypertensive CKD Patients The Aim Of This Study Was To Review The Results Of ABPM In CKD Patients Which Can Guide In Changing The Antihypertensive Therapy . Material and Methods: This Prospective Observational Study Having 63 Patients. All The Patients Fulfilling The Criteria Of CKD According To The KDIGO Guidelines And Above 18 Years Of Age Were Included In This Study Whose 24 Hour Ambulatory Blood Pressure Was Measured.Detailed History, Clinical Examination And Relevant Investigations Were Recorded Comparisons Of Various ABPM Characteristics WERE Done And P Value <0.005 Was Considered Significant. Results: Out Of 63 Patients (M:38,F:25)Maximum Patients (25.39%)Were In Age Group 61-70 Years (M:61-70,F:41-45).51(80.95%)Patients Were On Dialysis And 12 (19.04%)Patients Were Not On Dialysis. In This Study 57 Patients Had Hypertension, 44 Had DM,16 Had IHD.In This Study 2(3.17%) Patients Were CKD Stage I,5(7.93%) Were Stage II,1(1.58%) Was Stage lll, 6(9.52%) Were Stage IV And 49 (77.77%) Were Stage V.Out Of Total 16(25.39%) Patients Were Dippers ,21 (33.33%) Were Non Dippers, 21(33.33%) Were Reverse Dippers And 5 (7.93%) Were Extreme Dippers..Mean ABPM Systolic BP ,Mean ABPM Diastolic BP,Mean PTA Systolic BP,Mean Arterial Pressure Were Significantly Higher In Male Patients which were On Dialysis Than Patient Not On Dialysis. Conclusion: ABPM is Superior Than Clinical Bp Monitoring In Predicting The Future Communications In CKD Patients Especially PTE,HBI MAP And Other Parameter To Guide To Formulate Treatment Protocol Identifying Such Patients Of Hypertension In Earlier Stages Of CKD,Helped In Morbidity Outcomes While Identifying In Later Stages Of CKD Helped In Mortality Benefits.